“The Ending that Never Ends” or The Posthumous Life of Musicians (Revista Argentina de Musicología, 2021)
No matter how comprehensive a biography seems to be, it is but the unfinished account of a life—just like someone’s death usually makes evident a series of pending issues. By taking into account the interactions of the living with the legacy of the dead and the way in which the past is continually reenacted and refashioned by virtue of those interactions, it is clear that there is also a social afterlife for the dead among the living. This article examines the analytical and epistemological challenges surrounding the study of musicians’ afterlives. Considering the lives and afterlives of Chano Pozo, Selena, Luis A. Calvo, Nat King Cole, Julián Carrillo, Clara Schumann, Johannes Brahms, and a couple of movie characters, at least three issues loom large in the article: the need of extending the limits of human agency towards the afterlife and the intermundane realm, the acts of forgery that are inherent to any attempt to reenact a life, and the transhistorical character of music and musicians’ lives.
Keywords: biography; musical afterlives; agency; reenactment; intermundane collaborations